Trends in Guidance and Counseling Technology Research: A Bibliometric Analysis of Publications in the Scopus Database - Mohamad Saripudin; Rike Ulandari; Desriani Rahmania; Mohamad Saripudin; Rike Ulandari (Universitas Negeri Malang, 2025)
The development of technology affects guidance and counseling services. Various technologies are used to facilitate access to practical guidance and counseling services. The primary purpose of this article is to determine research trends on the topic of technology in guidance and counseling. The method used in this study is Bibliometric Analysis with the help of R Studio Bibliosiny software. Bibliometric analysis is carried out in three steps: 1) determining the objectives and research questions; 2) developing research design; and 3) analyzing results and interpretations. This Bibliometric analysis uses the Scopus database. The research findings show: 1) Performance analysis shows that the development of technology research in guidance and counseling during 1959-2025 has increased in terms of quantity with an Annual Growth Rate of 7.06% and Productivity per active year of publication of 30.03; 2) Kraut et al.’s publication in 1998 regarding the Internet paradox became the most influential publication. Then, the Journal of Substance Abuse Treatment became the most impactful journal on the topic of guidance and counseling technology; 3) The United States became the most productive country publishing articles related to technology in guidance and counseling. Naslud Ja is the most active author collaborating with other authors; 4) Over the past five years, the most widely studied topics are therapy, exercise, machine learning, artificial intelligence, and drug therapy. Overall, it can be concluded that there is an increase in the number of publications, research trends, and interest in guidance and counseling technology research. Researchers in the field of guidance and counseling who are interested in publishing their work in the Scopus database or Scopus-indexed journals can focus their research on keywords that have emerged over the past five years.